Management Psychological Well-Being Sunan Kalijaga - Mulyono, Puput; Purnomo, Singgih (TSAQOFAH, 2024)
This research is motivated by the fact that the younger generation has a fragile mental condition that requires psychological well-being in order to maintain sanity. Sunan Kalijaga is one of the nine saints who became uswah hasanah, a good example that can inspire the younger generation to stay sane in crazy times. The purpose of the research is to examine aspects of psychological well-being in Sunan Kalijaga's works in the present context. This research method uses descriptive qualitative research method. The result of this research is that Sunan Kalijaga is to be a useful human being by way of topo ngrame, doing good in the midst of crowds of people, not being alone on a mountain away from people. Then continued with topo ngeli. Topo ngeli is the teaching of Sunan Kalijaga when he was ngeli or floating in the ocean to meet the Prophet Khidir.